Killer whale call frequency is similar across the oceans, but varies across sympatric ecotypes - Filatova, Olga A.; Miller, Patrick J. O.; Yurk, Harald; Samarra, Filipa I. P.; Hoyt, Erich; Ford, John K. B.; Matkin, Craig O.; Barrett-Lennard, Lance G. (The Journal of the Acoustical Society of America, 2015)
Killer whale populations may differ in genetics, morphology, ecology, and behavior. In the North Pacific, two sympatric populations ("resident" and "transient") specialize on different prey (fish and marine mammals) and retain reproductive isolation. In the eastern North Atlantic, whales from the same populations have been observed feeding on both fish and marine mammals. Fish-eating North Pacific "residents" are more genetically related to eastern North Atlantic killer whales than to sympatric mammal-eating "transients." In this paper, a comparison of frequency variables in killer whale calls recorded from four North Pacific resident, two North Pacific transient, and two eastern North Atlantic populations is reported to assess which factors drive the large-scale changes in call structure. Both low-frequency and high-frequency components of North Pacific transient killer whale calls have significantly lower frequencies than those of the North Pacific resident and North Atlantic populations. The difference in frequencies could be related to ecological specialization or to the phylogenetic history of these populations. North Pacific transient killer whales may have genetically inherited predisposition toward lower frequencies that may shape their learned repertoires. (C) 2015 Acoustical Society of America.